Photocatalytic Degradation of Phenol Red Using Titanium Dioxide (TiO₂)–Chitosan Composite Catalyst Assisted By Solar Energy - Taufiqur Rohman; Muhammad Ridwan Baidhowi; Utami Irawati (Jurnal Sains dan Terapan Kimia, 2025)
Phenol Red is a very water-soluble textile dye that belongs to the triphenylmethane dye class. In this study, a photocatalyst composite was synthesized by combining TiO2 as photocatalyst with chitosan as a solid support material. The aim of this research is to study what ratio of TiO2: Chitosan would yield the best-performing composites in catalysing the photodegradation of phenol red. This research also studied, the optimum dose of TiO2-chitosan for photodegradation of phenol red, and the effect of solar radiation time towards the photodegradation of phenol red. Into 100 mL of phenol red solution with an initial concentration of 25 ppm, chitosan beads and TiO2-Chitosan composites were added with various doses, i.e:  0.5:100, 1:100, 2:100, and 5:100 gram/mL. The mixtures were put into solar radiaton exposure for 6 hours, where the concentration of phenol red in the solution was analysed every 20 minutes. The highest degradation level of phenol red (72.84%) was achieved by using TiO2-Chitosan 5:10 composites, where the dose added was 5 grams of composite for in 100 mL sample along with a 6-hour of solar radiation exposure.